Analisis Kekuatan Tarik dan Impak Material Komposit Serat Rami dengan Menggunakan Metode Hand Lay Up - Ricco Zulvikal (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Natural fibers can be used as an alternative basic material for produce SNI helmet that are environmentally friendly. A huge potential of hemp fiber in Indonesia has not apply properly yet. This study propose to determine the ability of tensile strength and impact toughness in hemp fiber composites so that hemp fiber can be used as an alternative material for making SNI helmets. This study uses an unsaturated polyester 157 BQTN-EX resin matrix and MEKPO catalyst. Alkali treatment of the fibers uses 5% NaOH for 2 hours. The composite is made using the hand lay-up method. Variations volume fraction of hemp fiber used are 30%, 40%, 50%. The tensile testing process uses the ASTM D 638-03 standard and impact toughness testing uses the ASTM D 265-03 standard. Based on the research results, the highest tensile test results were obtained at variation on 30% fiber volume fraction is 18.30 MPa, for the highest impact toughness test results were obtained at variation on 50% fiber volume fraction is 0.0248 J/mm2. The greater the variation of the fiber volume fraction given, the lower the tensile strength value produced, while the higher the variation of the fiber volume fraction given, the greater the energy absorbed so that the impact price increases. Based on the test results, this hemp fiber composite needs to be considered as an alternative material to replace SNI helmet manufacturing.